A New Biomarker in Diagnostic in Spirometry Exams with the Application of Wavelets - Rodrigo G.G. Piva; Rodrigo Prior Bechelli; Aldo Artur Belardi (Journal of Advances in Applied & Computational Mathematics, 2018)
This article presents a new medical biomarker that can be use in spirometry tests. These biomarker was obtained through a set of tests, where Meyer wavelet was applied and allows through one statistical analysis of the data obtained in pulmonary exams, could be possible to obtain numerical indicators that assist the physician achieve diagnosis in patients pulmonary function as normal, obstructive or restrictive.